The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2230.2004.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognostic factors of cutaneous melanoma among Hong Kong Chinese

Abstract: Cutaneous melanoma is rare among Chinese people. The clinicopathologic features and prognostic factors of 63 Hong Kong ethnic Chinese cases were analysed. We found that the mean age of onset was 65.5 years with a female : male ratio of 1 : 1.33. Forty-two (66.7%) patients had their tumours on their feet. More than 50% had the acral lentiginous histologic subtype. The mean tumour thickness was 5.73 mm with 92.1% (n = 58) having a Clark's level of III or more. Of the tumours, 57.1% were ulcerated. Stage I and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…Sng et al (2009) reported CM incident rates in Singapore in two age groups: younger than 60 years, and older than 60 years. Luk et al (2004) reported that 57.1% of CM patients in Hong Kong received a diagnosis at age 60 or greater, while only 6.3% received a diagnosis at age 30 or younger, and no data was reported for patients between the age of 50 and 60 years old. In addition, Hui et al (2005) reported a mean age of 57.6 years for 32 Hong Kong CM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sng et al (2009) reported CM incident rates in Singapore in two age groups: younger than 60 years, and older than 60 years. Luk et al (2004) reported that 57.1% of CM patients in Hong Kong received a diagnosis at age 60 or greater, while only 6.3% received a diagnosis at age 30 or younger, and no data was reported for patients between the age of 50 and 60 years old. In addition, Hui et al (2005) reported a mean age of 57.6 years for 32 Hong Kong CM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are sex-related differences in CM mortality rates (Lasithiotakis et al, 2008) with men being at a greater risk of developing and dying from CM (Luk et al, 2004; Makredes, Hui & Kimball, 2010). In Hong Kong, the female-to-male incidence rate is 1:1.22 (Luk et al, 2004), and the mortality rate is 1:1.35 (Makredes, Hui & Kimball, 2010). Few studies exist investigating the cumulative effects of risk factors on the mortality rate of CM in East Asian populations; this study aims to address this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Asians living in their native countries have a high incidence of acral lentiginous tumors, comprising a majority of the cutaneous melanomas diagnosed [18][19][20]22,26,34]. Whether or not other forms of cutaneous melanoma would be identified more commonly in this population with increased recognition or screening programs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Plantar acral melanomas also constituted onefourth of all melanomas in a study from Manipal [9]. In Hong Kong Chinese (who have a low incidence of cutaneous melanomas like India) cutaneous melanoma was found predominantly at an older age with the acral lentiginous histologic type located mainly on the feet [10]. Only 9/32 anal melanomas reported from Delhi were clinically diagnosed as melanomas [11].…”
Section: Discussionmentioning
confidence: 99%